Ex-ante assessment of the implementation of an energy management policy in Northern Africa. (1st January 2014) - Fasone, Vincenzo; Giuffrè, Tullio; Messineo, Antonio
Energy management policy is an important part of the environmental and climate change policies and permits to reach the goals of improved security of energy supply, economic efficiency and of greenhouse gases emissions reduction. In these years, the use of market mechanisms to meet environmental objectives is really growing, with the most important example to use of emissions trading schemes to control greenhouse gases emissions, e.g., EU's climate and energy policy sets a 20% reduction in energy consumption to be achieved by 2020 through energy-efficiency improvements. In this context, this paper aims to assess whether it is possible to transfer to the North African context the lesson learnt from the more representative experiences or if it is necessary to adopt an ad hoc system.